Cell-free DNA promoter hypermethylation in plasma as a diagnostic marker for pancreatic adenocarcinoma. Issue 1 (December 2016) - Henriksen, Stine; Madsen, Poul; Larsen, Anders; Johansen, Martin; Drewes, Asbjørn; Pedersen, Inge; Krarup, Henrik; Thorlacius-Ussing, Ole
Abstract Background Pancreatic cancer has a 5-year survival rate of only 5–7%. Difficulties in detecting pancreatic cancer at early stages results in the high mortality and substantiates the need for additional diagnostic tools. Surgery is the only curative treatment and unfortunately only possible in localized tumours. A diagnostic biomarker for pancreatic cancer will have a major impact on patient survival by facilitating early detection and the possibility for curative treatment. DNA promoter hypermethylation is a mechanism of early carcinogenesis, which can cause inactivation of tumour suppressor genes. The aim of this study was to examine promoter hypermethylation in a panel of selected genes from cell-free DNA, as a diagnostic marker for pancreatic adenocarcinoma. Methods Patients with suspected or biopsy-verified pancreatic cancer were included prospectively and consecutively. Patients with chronic/acute pancreatitis were included as additional benign control groups. Based on an optimized accelerated bisulfite treatment protocol, methylation-specific PCR of a 28 gene panel was performed on plasma samples. A diagnostic prediction model was developed by multivariable logistic regression analysis using backward stepwise elimination. Results Patients with pancreatic adenocarcinoma (n  = 95), chronic pancreatitis (n  = 97) and acute pancreatitis (n  = 59) and patients screened, but negative for pancreatic adenocarcinoma (n  = 27), were included. The difference in mean number of methylated genes in the cancer group (8.41 (95% CI 7.62–9.20)) vs the total control group (4.74 (95% CI 4.40–5.08)) was highly significant (p  < 0.001). A diagnostic prediction model (age >65, BMP3, RASSF1A, BNC1, MESTv2, TFPI2, APC, SFRP1 andSFRP2 ) had an area under the curve of 0.86 (sensitivity 76%, specificity 83%). The model performance was independent of cancer stage. Conclusions Cell-free DNA promoter hypermethylation has the potential to be a diagnostic marker for pancreatic adenocarcinoma and differentiate between malignant and benign pancreatic disease. This study brings us closer to a clinical useful diagnostic marker for pancreatic cancer, which is urgently needed. External validation is, however, required before the test can be applied in the clinic. Trial registration ClinicalTrials.gov, NCT02079363